2015
DOI: 10.14257/astl.2015.103.10
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking disposition, problem solving process, and empathy among Nursing Students

Abstract: The purpose of this study was to examine the relationships between nursing students' empathy and their critical thinking disposition and problem solving process. For this purpose, 246 nursing students were surveyed using a structured questionnaire on their empathy, critical thinking disposition, and problem solving process. According to the results of data analyses, the subjects' critical thinking disposition was in a positive correlation with their fantasy, perspective taking, and empathetic concern, and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“… 1 , 2 Critical thinking pervades all human activities via the processes of thinking and reflection and is key in acquiring all of the abovementioned abilities. 3 , 4 In recent years, an increasing number of educators have realized the disadvantages of traditional teaching methods. Nursing educators have therefore attempted to implement various teaching methods, to improve critical thinking skills in nursing students.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Critical thinking pervades all human activities via the processes of thinking and reflection and is key in acquiring all of the abovementioned abilities. 3 , 4 In recent years, an increasing number of educators have realized the disadvantages of traditional teaching methods. Nursing educators have therefore attempted to implement various teaching methods, to improve critical thinking skills in nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…The results of many studies show that critical thinking, as a valid method in thinking and tendency toward critical thinking plays an important role in personal and social situations; as many studies emphasize a significant relationship between the tendency toward critical thinking, academic achievement, problem-solving skills, and caring behaviors (15)(16)(17)(18)(19)(20)(21). Despite the great importance of critical thinking in decision-making and the improvement of nurses' clinical competence, the researchers stated that little attention is paid to the development and promotion of critical thinking in nursing (22).…”
Section: Introductionmentioning
confidence: 99%
“…However, good interpretive ability did not show statistically significant ability in critical thinking. Jeong (2015) found that critical thinking disposition was positively correlated with perspective taking (r=0.482, p<0.001), fantasy (r=0.227, p<0.001), and empathic concern (r=0.195, p=0.002) 17 . Woo & Tak, (2015) illustrated that critical thinking disposition positively correlates with caring perception (r=0.174, p=0.024) and professional self-concept (r=0.343, p=0.022) 18 .…”
Section: Discussionmentioning
confidence: 99%